The Effect of Teaching Methods and Linguistic Competence on the Students’ Writing Achievement - Nurmala Nurmala; Didik Santoso; Sri Minda Murni (Universitas Negeri Medan, 2015)
The objectives of the research were to investigate: 1) the students’ achievement in writing narrative text taught by using task-based learning higher than those taught by direct instruction, 2) the students’ achievement in writing narrative text with high linguistic competence is higher than those with low linguistic competence, 3) there is interaction between teaching methods and linguistic competence on students’ achievement in writing narrative text. It was an experimental research with the population of students at State Senior High School (SMAN) 2 Kisaran 2012/2013 academic year. The sample was selected by applying multistage cluster random sampling. The data collected were analyzed by applying two-way analysis of variance (2x2 ANOVA). The findings indicated that: 1) the students’ achievement in writing narrative text taught by using task-based learning is higher using direct instruction (80 > 67), 2) the students’ achievement in writing narrative text with high linguistic competence is higher than students with low linguistic competence, (80 > 65), 3) there is interaction between teaching methods and linguistic competence on students’ achievement in writing narrative text (sig. = 0.00 < 0.05). Based on the findings, it is suggested that task-based learning method should be applied in English teaching to develop the students’ writing achievement. Key words: writing; task-based learning; direct instruction; linguistic competence.